2015
DOI: 10.1111/ejh.12488
|View full text |Cite
|
Sign up to set email alerts
|

Familial thrombotic risk based on the genetic background of Protein C Deficiency in a Portuguese Study

Abstract: Introduction Inherited protein C (PC) deficiency is a well‐known risk factor for venous thrombosis (VT). Plasma PC levels are reliable in moderate to severe deficiencies; however, in mildly deficient individuals, the levels may overlap with those considered normal. Genetic studies of PROC, which encodes PC, could help identify carriers; genome‐wide association studies (GWAS) have shown that approximately 50% of phenotypic variation in PC deficiency is caused by the cumulative effects of mutations in several ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…As we did not study PROC deep intronic regions, we cannot exclude that a few detrimental mutations were missed in our study. Concerning PROC promoter polymorphisms at positions 28 In a small family cohort of carriers of PROC detrimental mutations, retrospectively studied, Fidalgo et al reported a higher number of VTEs in CG homozygotes than in carriers of other PROC promoter genotypes; in our study, this was not observed either in the whole population or in the subgroup of subjects carrying the mutations previously studied by Fidalgo et al 45 Genome-wide association studies of PC have been conducted with aim of finding genetic determinants located outside the PROC locus. The GAIT study estimated that sequence variations in other genes than PROC could explain approximately half of the phenotypic variation in PC level.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…As we did not study PROC deep intronic regions, we cannot exclude that a few detrimental mutations were missed in our study. Concerning PROC promoter polymorphisms at positions 28 In a small family cohort of carriers of PROC detrimental mutations, retrospectively studied, Fidalgo et al reported a higher number of VTEs in CG homozygotes than in carriers of other PROC promoter genotypes; in our study, this was not observed either in the whole population or in the subgroup of subjects carrying the mutations previously studied by Fidalgo et al 45 Genome-wide association studies of PC have been conducted with aim of finding genetic determinants located outside the PROC locus. The GAIT study estimated that sequence variations in other genes than PROC could explain approximately half of the phenotypic variation in PC level.…”
Section: Discussioncontrasting
confidence: 49%
“…47 Fidalgo et al reported that PROCR H3 carrying could explain differences in plasma PC levels among carriers of PROC mutations. 45 Interestingly, high and even sometimes very high PC (> 160%) levels have been observed in H3 homozygous carriers. 48 Unfortunately, genotyping for this haplotype could not be performed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to healthy individuals, heterozygous individuals have PC levels that are approximately 50% of the standard value. Generally, no clinical symptoms or delayed venous thromboembolism occur [ 8 ]. Our patients had PC activities of 53%, 40%, and 45%.…”
Section: Discussionmentioning
confidence: 99%
“…These papers were not exactly focused on MDR in cases of AT, PC, and PS deficiency. More specific results have mainly been provided in studies where molecular diagnostics was provided by Sanger sequencing [10,11,[22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Missense mutations c.1301T > C (p.Val434Ala), c.1019C > T (p.Thr340Met), and c.1106C > T (p.Pro369Leu) were identified in exon 9. They have been previously identified in probands with DVT or a positive family history of thrombosis [10,30,33]. The stop-loss variant c.1384T > C (p.Ter462Gln) found in female probands has been previously described [23].…”
Section: Protein C Deficiencymentioning
confidence: 98%